2010
DOI: 10.1123/jpah.7.4.475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elimination Games on Physical Activity and Psychosocial Responses in Children

Abstract: Background:This study evaluated the effect of elimination and nonelimination games on objectively measured physical activity and psychosocial responses in children.Methods:A total of 29 children in grades 4 to 6 (65.5% male; 10.5 ± 1.0 years old) wore an accelerometer while participating in 2 elimination and 2 nonelimination games. Activity counts were collected using a 30-second epoch and converted to METs to determine minutes spent in sedentary behavior and light, moderate, vigorous, and moderate-to-vigorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…Traditional activities/games, such as tag and kickball, included children standing and waiting for their turn and/or children being eliminated from games. This translates into children spending more time in sedentary behavior when playing these games (Foster et al, 2010; Trost et al,2008). Thus, while free-play can be part of activity offerings, providing high quality structured activities will assist all children to meet physical activity recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional activities/games, such as tag and kickball, included children standing and waiting for their turn and/or children being eliminated from games. This translates into children spending more time in sedentary behavior when playing these games (Foster et al, 2010; Trost et al,2008). Thus, while free-play can be part of activity offerings, providing high quality structured activities will assist all children to meet physical activity recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] A previous study found that adult-led games, compared to free play opportunities, had a higher amount of inactive elements, such as games with elimination and children standing and waiting in lines. 24 This is consistent with another study 13 that reported adult-led games frequently consisted of dodgeball and kickball, two commonly played games that eliminate children or have long lines of children.…”
Section: Discussionmentioning
confidence: 99%
“…Time spent in light (200 counts to <4 METS), moderate PA (4 to <7 METS), vigorous PA (≥7 METS), and moderate-to-vigorous PA (≥4 METS) was determined by Freedson's MET prediction equation [29]. The cutpoints chosen for the intensity levels are commonly used in children [4,30].…”
Section: Methodsmentioning
confidence: 99%